QIRA’AH INTERPRETATION ON Q.S. AL MAIDAH [5]:6: Shia Perspectives from Makârim Shirazî and Țabâțabâ’î’ - Yuliarto, Udi; Husnaini, Ica Fauziah; el-Feyza, Muhafizah; Putra, Hepni; Hamid, Hudaili Abdul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The interpretations of Q.S. al-Mâidah [5]:6 by Makârim Shirazî and Țabâțabâ’î focus on the meaning and practical implication of wudu, particularly concerning the word ‘arjulakum’ which holds two possible meanings based on different qirâ’ah. These differences generate various understandings and be distinguishing factors among Islamic mazhabs. One of them is Shia which considers the recitation a key basis for performing five obligatory prayers. This article presents and analyzes the interpretation of Q.S. al-Mâidah [5]:6 by Makârim Shirazî and Țabâțabâ’î’, two prominent exegetes in Shia tradition. The study adopts a qualitative approach using descriptive-analytical methods and is conducted through library research. Data were analyzed using content analysis. The findings reveal that both exegetes center their interpretation on the word ‘wa arjulakum’, read either with a fathah or a kasrah. Shirazî and Țabâțabâ’î’, along with majority of Shia scholars, affirm and favor the qirâ’ah with kasrah (wa arjulikum), implying the command to wipe (rather than wash) the feet during wudu. This distinction is also reflected in their explanations regarding the extent of the area to be wiped. This tafsir implication shows obedience to teaching conveyed by ahl al-bayt, and strengthens the main principal in Shia that Quranic interpretation is closely intertwined with hadiths originating from ahl al-bayt. The article contributes to a broader discourse on interpretive framework within Islamic traditions, highlighting Shia interpretations of qirâ’ah and narration which shape ritual practice. It also provides a detailed case study of how linguistic variation affects Islamic legal thought.",